Responsibility to Protect
XIII, 271 p.
Keywords: In 2005, the international community unanimously endorsed a revolutionary norm that has the potential to end genocide and other atrocity crimes in our time. Despite its endorsement at the highest political level and the general feeling of the American public that "something needs to be done" to prevent and stop atrocity crimes, the Responsibility to Protect (R2P) is very much absent from public thinking and the political agenda in the United States. Written by a stellar cast of authors, this book informs the public and leadership about R2P and its potential. It will also influence the academic, community and political debates by providing crucial insights on how to move R2P from rhetoric to action.